Do online assessed self-report and behavioral measures of impulsivity-related constructs predict onset of substance use in adolescents?. (June 2015) - Janssen, Tim; Larsen, Helle; Peeters, Margot; Boendermaker, Wouter J.; Vollebergh, Wilma A.M.; Wiers, Reinout W.
Abstract: Introduction: To prospectively predict the onset of use of alcohol, cigarettes and marijuana among Dutch adolescents, using behavioral and self-report measures of impulsivity-related facets. Specifically, we investigated whether behavioral measures of impulsivity predicted the onset of substance use above and beyond self-report measures of impulsivity and sensation seeking in an online sample. Methods: Self-report and behavioral data from 284 adolescents (195 girls, mean age = 14.8 years, SD = 1.26) were collected at four time points over a period of two years, using an online survey system. Impulsivity-related facets were assessed at time point 1 with the Delay Discounting Task, the Balloon Analogue Risk Task and the Passive Avoidance Learning Task. We conducted logistic regression analysis to examine whether behavioral and self-report measures uniquely predicted onset of alcohol use, heavy episodic drinking, smoking and marijuana use. Results: Onset of cigarette smoking was associated with behavioral assessment of impulsive decision making, but not after controlling for self-reported impulsivity and sensation seeking. Behavioral measures were sometimes associated with, but appeared not to prospectively predict, the onset of substance use in this online sample after controlling for self-report measures. Conclusions: Based on the present results, the added value of online behavioral assessment of impulsivity-related factors in the prediction of onset of substance use was not confirmed. We suggest that factors specific to each behavioral task underlie their lack of prediction and suggest that future research addresses limitations of current behavioral tasks to increase their validity in online testing. Highlights: We predicted substance use onset with self-report and behavioral impulsivity. Self-report impulsivity, not behavioral impulsivity, predicted onset overall. Delay discounting predicted smoking, but not after other predictors were included.